An efficient cross layer based channel reservation method for vehicular networks. (10th August 2013) - Saritha, V.; Madhu Viswanatham, V.
SUMMARY The swift growth of the mobile users and limited availability of bandwidth lead to the requirement of effective channel allocation process. Channel allocation becomes tedious in vehicular ad hoc network, as the mobility of the nodes is high. So, in this paper, we propose a method called as cross layer based channel reservation with preemption (CCRP) method that performs channel allocation process by estimating the handoffs in vehicular ad hoc networks. The time estimated is communicated from physical layer to medium access control layer using a cross‐layer design. The reusability concept is used, and the channels are divided into three groups. The different cells acquire different groups based on the database status and exclusively to avoid interference. Preemption is incorporated to give the highest priority to real time originating calls and real time handoff calls. The performance of the proposed method, CCRP, is compared with the legacy systems such as cooperative reservation of service channels and very fast handover scheme in terms of dropping probability, blocking probability, and handoff latency. The results show that the proposed algorithm, CCRP, performs better in comparison. Copyright © 2013 John Wiley & Sons, Ltd.